Skin response to a carcinogen involves the xenobiotic receptor pregnane X receptor. Issue 11 (14th July 2015) - Elentner, Andreas; Ortner, Daniela; Clausen, Björn; Gonzalez, Frank J.; Fernández‐Salguero, Pedro M.; Schmuth, Matthias; Dubrac, Sandrine
Abstract: Skin is in daily contact with potentially harmful molecules from the environment such as cigarette smoke, automobile emissions, industrial soot and groundwater. Pregnane X receptor (PXR) is a transcription factor expressed in liver and intestine that is activated by xenobiotic chemicals including drugs and environmental pollutants. Topical application of the tumor initiator 7, 12‐dimethylbenz(a)anthracene (DMBA) enhances Pxr, Cyp1a1, Cyp1b1 and Cyp3a11, but not Ahr expression in the skin. Surprisingly, DMBA‐induced Pxr upregulation is largely impaired in Langerin + cell‐depleted skin, suggesting that DMBA mainly triggers Pxr in Langerin + cells. Furthermore, PXR deficiency protects from DNA damage in epidermal cells but to a lesser extent than aryl hydrocarbon receptor (AHR) deficiency. Interestingly, skin exposure to low doses of DMBA induces migration of PXR‐deficient but not of wild‐type and AHR‐deficient Langerhans cells (LCs). PXR‐humanized mice show a marked increase in DNA damage to epidermal cells after topical application of DMBA, demonstrating relevance of these findings in human tissue. This is the first report suggesting that carcinogens might trigger PXR in epidermal cells, particularly in LCs, thus leading to DNA damage. Further studies are required to better delineate the role of PXR in cutaneous carcinogenesis.